Experimental Studies on Physicochemical Parameters of Water Samples before and after Treatment with a Cold Atmospheric Plasma Jet and its Optical Characterization. (13th January 2021) - Baniya, Hom Bahadur; Guragain, Rajesh Prakash; Panta, Gobinda Prasad; Dhungana, Santosh; Chhetri, Ganesh Kuwar; Joshi, Ujjwal Man; Pandey, Bishnu Prasad; Subedi, Deepak Prasad
Abstract : Cold plasma-liquid interaction becomes a growing interdisciplinary area of research involving plasma physics, fluid science, and chemistry. Plasma-liquid interaction has gained more interest over the last many years due to its potential applications in different fields. Cold atmospheric plasma jet is an emerging technology for surface drinking water treatment to improve quality and surface modification that is chemical-free and eco-friendly. Cold plasma treatment of water samples results in changes in turbidity, pH, and conductivity and in the formation of reactive oxygen and nitrogen species (RONS). As a result, plasma-activated water has a different chemical composition than water and can serve as an alternative technique for microbial disinfection. CAPJ has been generated by a high voltage 5 kV and a high frequency 19.56 kHz power supply. The discharge has been characterized by an optical method. To characterize the cold atmospheric pressure argon plasma jet, discharge plume temperature, and electron rotational and vibrational temperature have been determined. Cold atmospheric argon plasma jet produced at atmospheric condition contains high energetic electrons, ions, UV radiation, reactive oxygen, and nitrogen species named as cold plasma which has a wide range of applications in the biomedical industry, as well as in water treatment. Nowadays, researches have been carried out on ozonation through plasma jet interaction with surface drinking water. In this paper, we compare the change in physical and chemical parameters of surface water used for drinking purposes. The significant change in the physical parameters such as pH, turbidity, and electrical conductivity was studied. In addition, the significant changes in the concentration and absorbance of nitrate, ferrous, and chromium ions with respect to treatment time were studied. Our results showed that plasma jet interaction with surface drinking water samples can be useful for the improvement of water quality and an indicator for which reactive species play an important role in plasma sterilization.